EVALUASI KOLEKSI REFERENSI DIPERPUSTAKAAN MAN 1 PEKANBARU - Sudiar, Nining; H, Rosman; Mafar, Fiqru (Jurnal Ilmu Budaya, 2018)
This research aims to analyze the availabity of reference collections in library of MAN 1 Pekanbaru. This research is quantitative analysis. It uses observation, questionnaire and documentation techniques to collect the data. The result shows that the library MAN1 Pekanbaru has 6 types of reference collections from 10 types of reference collection, base on National Standards of Library. The types of reference collection available are Scripture, Dictionary, Encyclopedia, Atlas, map, and goverment regulation. The important collections which are not yet available among thers: biography, science dictionary, directory and almanac calendar.